NIPAH VIRUS: CLINICAL PERSPECTIVES ON AN EMERGING PRIORITY PATHOGEN - Aleksandra Mączyńska; Marta Zawadzka; Maria Wojcieszek; Maksymilian Czarnota; Magdalena Fidelis; Dominika Gacka; Zuzanna Tanç; Noor Alhuda Al-karawi; Paulina Kędziorek; Wiktoria Szumlińska; Aleksandra Żołnierek; Katarzyna Gondek (International Journal of Innovative Technologies in Social Science, 2026)
The emergence of zoonotic viral diseases has significantly impacted public health, the global economy, and societal structures in recent years. The World Health Organization's 2024 updated R&D Blueprint report identifies infectious agents posing the greatest epidemiological threats. Among them is the Nipah virus (NiV), a highly lethal paramyxovirus naturally harboured by fruit bats, which typically causes severe respiratory distress and encephalitis in humans. Moreover, the NiV exhibits the capacity to infect a wide range of mammalian species, including livestock and domestic pets.  The secretions and excretions of these animals can potentially serve as sources of human infection. This presents both a direct health risk and an indirect one, due to losses in agriculture and associated economic consequences. After the first outbreak in Malaysia (1998–1999), in addition to decontamination measures, mass culling of pigs was carried out. Although Malaysia has been declared free of NiV infection, new cases continue to emerge almost annually in Bangladesh and India, with the most recent reported in 2025. Given the current scale of human migration, the global nature of food transportation, and other facets of globalization, it is imperative to prepare for the potential spread of the disease of a magnitude similar to COVID-19. To date, no targeted therapies or vaccines have been approved. Given this situation, the primary objective of the present work is to raise awareness among clinicians regarding the characteristics and pathogenicity of NiV, as well as the practical aspects related to the recognition, diagnosis, and treatment of the infection.